APPLICATION OF ROLLING AREOLA MASSAGE USING JITU OIL AND RELAXATION OF MUROTTAL AL-QURAN ON SATISFACTION OF BREASTFEEDING MOTHERS - Ningsih, Dewi Andariya; Sakinah, Innama; Hikmah, Raudatul (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
Complementary therapies such as areola and booster massage can effectively support the production of breast milk. Mothers will be satisfied with nursing if there is maximum milk production. This is where breastfeeding succeeds. Although Al-Quran murottal and further relaxation from Jitu Oil have many advantages, nursing moms have not always used them to their full potential. The purpose of this study was to determine the effectiveness of Rolling Areola Massage Using Jitu Oil and Al-Quran Murottal Relaxation on the satisfaction of breastfeeding mothers. The research population with total sampling with a total of 64 respondents. Instrument measurement using Pearson Product Moment Validity Test. Pre and post test results using Kolmogorov Smirnov Normality Test and chi square test. Interpretation of the Wilcoxon test results obtained p0.001 which means that breastfeeding satisfaction between pretest and posttest is significantly different with all respondents experiencing an increase in breastfeeding satisfaction. Efforts to increase maternal satisfaction in breastfeeding need to be a breastfeeding promotion strategy. A mother who is satisfied with breastfeeding can influence other mothers to do the same, making the breastfeeding satisfaction approach more relevant. Therefore, strategies to increase mothers' satisfaction with breastfeeding should be incorporated into exclusive breastfeeding promotion programmes.